Avant-Garde 3: Experimental Cinema, 1922-1954 - Cavalcanti, Alberto; Peterson, Sidney; Kirsanov, Dmitrij (Kino on Video, 2009)
From the little theaters of the 1920s to the ad hoc film societies of the '50s, avant-garde cinema knew no established form and held no predictable position. The boundaries of its history are still hotly debated, but its rough sensibilities informed and permeated the city symphonies of Alberto Cavalcanti, the visual music of Mary Ellen Bute and John Whitney, the classroom films of Sidney Peterson, the confessional film poems of Willard Maas and John E. Schmitz, the Lettrist cinema of Marc'O, and even marginal exploitation films and home movies. Drawn from the rich collections of Raymond Rohauer and the George Eastman House, Kino's third volume of experimental films continues to illuminate the degree to which cinema's evolution has been influenced by those filmmakers who occupy its periphery. [Cover]